Clinical and Genetic Characteristics in Young, Glucocorticoid-Naive Boys With Duchenne Muscular Dystrophy. (25th January 2022) - Schiava, Marianela; Amos, Rachel; VanRuiten, Henriette; McDermott, Michael P.; Martens, Williams B.; Gregory, Stephanie; Mayhew, Anna; McColl, Elaine; Tawil, Rabi; Willis, Tracey; Bushby, Kate; Griggs, Robert C.; et al.
Abstract : Background and Objectives: Duchenne muscular dystrophy (DMD) is a pediatric neuromuscular disorder caused by mutations in the dystrophin gene. Genotype-phenotype associations have been examined in glucocorticoid-treated boys, but there are few data on the young glucocorticoid-naive DMD population. A sample of young glucocorticoid-naive DMD boys is described, and genotype-phenotype associations are investigated. Methods: Screening and baseline data were collected for all the participants in the Finding the Optimum Corticosteroid Regime for Duchenne Muscular Dystrophy (FOR-DMD) study, an international, multicenter, randomized, double-blind, clinical trial comparing 3 glucocorticoid regimens in glucocorticoid-naive, genetically confirmed boys with DMD between 4 and <8 years of age. Results: One hundred ninety-six boys were recruited. The mean ± SD age at randomization was 5.8 ± 1.0 years. The predominant mutation type was out-of-frame deletions (67.4%, 130 of 193), of which 68.5% (89 of 130) were amenable to exon skipping. The most frequent mutations were deletions amenable to exon 51 skipping (13.0%, 25 of 193). Stop codon mutations accounted for 10.4% (20 of 193). The mean age at first parental concerns was 29.8 ± 18.7 months; the mean age at genetic diagnosis was 53.9 ± 21.9 months; and the mean diagnostic delay was 25.9 ± 18.2 months. The mean diagnostic delay for boys diagnosed after an incidental finding of isolated hyperCKemia (n = 19) was 6.4 ± 7.4 months. The mean ages at independent walking and talking in sentences were 17.1 ± 4.2 and 29.0 ± 10.7 months, respectively. Median height percentiles were below the 25th percentile regardless of age group. No genotype-phenotype associations were identified expect for boys with exon 8 skippable deletions, who had better performance on time to walk/run 10 m ( p = 0.02) compared to boys with deletions not amenable to skipping. Discussion: This study describes clinical and genetic characteristics of a sample of young glucocorticoid-naive boys with DMD. A low threshold for creatine kinase testing can lead to an earlier diagnosis. Motor and speech delays were common presenting symptoms. The effects of low pretreatment height on growth and adult height require further study. These findings may promote earlier recognition of DMD and inform study design for future clinical trials. Trial Registration Information: ClinicalTrials.gov Identifier: NCT01603407.